Phase equilibria and dielectric properties of Bi3+(5/2)xMg2−xNb3–(3/2)xO14−x cubic pyrochlores - Tan, P. Y.; Tan, Kar Ban; Khaw, Chwin Chieh; Zainal, Zulkarnain; Chen, Soo Kien; Chon, Mun Ping (Elsevier, 2014)
Subsolidus pyrochlores with the proposed formula, Bi 3+(5/2)x Mg 2−x Nb 3−(3/2)x O 14−x (0.14≤x≤0.22) were successfully synthesised at the firing temperature of 1025°C using conventional solid-state reaction. The excess Bi 3+ charge was offset by removal of relative proportion of Mg 2+ and Nb 5+ together with creation of oxygen non-stoichiometry in order to preserve electroneutrality of the system. These samples were crystallised in cubic structure with space group of Fd3m, No. 227 and their refined lattice parameters were in the range of 10.5706 (3)–10.5797 (7)Å. The surface morphologies of the samples as confirmed by scanning electron microscopy analysis were of irregular shaped grains while their crystallite sizes of ~30–85nm were calculated using the Scherrer equation and the Williamson–Hall method. No thermal event was discernable indicating these pyrochlores were thermally stable within a studied temperature range of ~30–1000°C. The recorded dielectric constants of Bi 3+(5/2)x Mg 2−x Nb 3−(3/2)x O 14−x (0.14≤x≤0.22) subsolidus pyrochlores were generally above ~160 and their dielectric losses were in the order of 10 −4 –10 −3 at the frequency of 1MHz and temperature of ~30°C. Meanwhile, these ceramic samples also exhibited negative temperature coefficient of relative permittivity between −528 and −742ppm/°C in the temperature range of ~30–300°C.